PENGARUH LINGKUNGAN KERJA, KEMAMPUAN KERJA DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA KARYAWAN STUDI KASUS PADA PT. JACCS MPM FINANCE INDONESIA CABANG KEDIRI - H.M, Mefrinta Nadya; Meilina, Restin; Raharjo, Itot Bian (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The purpose of this study is to identify the variables that influence employee performance. This study was carried out. at PT JACCS MPM Finance Indonesia Kediri Branch. Employee performance is the study's dependent variable, whereas the work environment and independent variables are work abilities and individual characteristics. Data was obtained from employees of PT JACCS MPM Finance Indonesia Kediri Branch. With the saturated sampling technique, 40 employees were sampled. To create a thorough picture of the link between one variable and another, the study strategy employed multiple linear regression analysis techniques with a 5% confidence level. According to the findings of the t-test research, work environment variables, work abilities, and individual traits, all have a substantial effect on employee performance. According to the F test results, the variables of work environment, job ability, and individual characteristics all have a substantial effect on employee performance at the same time. The modified R Square value is 0.573, indicating a 57.3% influence of the work environment, job aptitude, and individual attributes on employee performance.